Problematic and extensive YouTube use: first hand reports - Klobas, Jane E; McGill, Tanya J; Moghavvemi, Sedigheh; Paramanathan, Tanuosha (Online information review, 2019)
Purpose The purpose of this paper is to present brief YouTube life stories to learn about how extensive users experience YouTube use and manage (or fail to manage) their use. It also explores the consequences of different types of extensive use. Design/methodology/approach In this paper, a biographical approach was used. Nine students who used YouTube for two or more hours every day were guided to tell life stories of their introduction to YouTube, subsequent use and critical events associated with YouTube use. Thematic analysis distinguished between non-problematic, compulsive and addicted users. Three single case life stories illustrate the experiences of users in each category. Findings These extensive YouTube users tell similar stories of informal learning from early interaction with the platform. For some, extensive YouTube use became problematic; for others, it remained functional. Similar to other social platforms, users unable to regulate use became compulsive users and some users can become addicted. While the symptoms of YouTube addiction are similar to other online addictions, compulsive YouTube use is driven more by algorithm-generated content chaining than overt social interaction. Originality/value The paper introduces life stories as a way to present case studies of social media use. The distinction between extensive, but functional, and problematic YouTube use illustrates how extensive social media use is not necessarily dysfunctional. User education for self-regulation of YouTube use is recommended.